Human DNA Helicase B as a Candidate for Unwinding Secondary CGG Repeat Structures at the Fragile X Mental Retardation Gene - Guler, Gulfem D.; Rosenwaks, Zev; Gerhardt, Jeannine (Frontiers in Molecular Neuroscience, 2018)
The fragile X syndrome is caused by a CGG repeat expansion at the fragile X mental retardation (FMR1) gene. FMR1 alleles with more than 200 CGG repeats bear chromosomal fragility when cells experience folate deficiency. CGG repeats were reported to be able to form secondary structures, such as hairpins, in vitro. When such secondary structures are formed, repeats can lead to replication fork stalling even in the absence of any additional perturbation. Indeed, it was recently shown that the replication forks stall at the endogenous FMR1 locus in unaffected and FXS cells, suggesting the formation of secondary repeat structures at the FMR1 gene in vivo. If not dealt with properly replication fork stalling can lead to polymerase slippage and repeat expansion as well as fragile site expression. Despite the presence of repeat structures at the FMR1 locus, chromosomal fragility is only expressed under replicative stress suggesting the existence of potential molecular mechanisms that help the replication fork progress through these repeat regions. DNA helicases are known to aid replication forks progress through repetitive DNA sequences. Yet, the identity of the DNA helicase(s) responsible for unwinding the CGG repeats at FMR1 locus is not known. We found that the human DNA helicase B (HDHB) may provide an answer for this question. We used chromatin-immunoprecipitation assay to study the FMR1 region and common fragile sites, and asked whether HDHB may localize at replication forks stalled at repetitive regions even in unperturbed cells. HDHB was strongly enriched in S-phase at the repetitive DNA